Impact of Pregnant Women’s Depression State upon their Pregnancy Outcomes at Maternity Hospitals in Baghdad City - Raghad Z. Dosar; Najmah M. Meran (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: To assess the impact of pregnant women’s depression state upon their pregnancy outcome Methodology: A descriptive purposive study was used to assess the impact of pregnant women’s depression state on their pregnancy outcomes. The study was conducted from (22nd \ September \ 2020 to 15th \ February \ 2021). A non-probability sample (purposive sample) was selected from 100 women. Data were collected through an interview with the mother in the counseling clinic, during the third trimester of pregnancy, as well as after childbirth in the labour wards to assess the outcome of pregnancy. Data were analyzed through descriptive statistics (frequency and percentages).Results: The most important thing observed in this study was the negative pregnancy outcome for women suffering from depression during pregnancy. Low birth weight (31%), premature labor (22%), stillbirth (2%), intrauterine growth restriction (1%)Recommendations: The study recommends according to the results. We suggest that health care providers pay attention to the mental state of pregnant women. Providing training and scheduling support during pregnancy for mothers in order to identify risk factors and achieve skills and knowledge to support mothers, as well as providing a soothing atmosphere to ensure a peaceful environment for pregnant women.